Development of a pH-sensitive functionalized metal organic framework: in vitro study for simultaneous delivery of doxorubicin and cyclophosphamide in breast cancer. Issue 53 (15th October 2021) - Singh, Ragini; Kumar, Binayak; Sahu, Ram Krishna; Kumari, Soni; Jha, Chandan Bhogendra; Singh, Nahar; Mathur, Rashi; Hedau, Suresh T.
Abstract : Exploration of an efficient dual-drug based nanocarrier with high drug loading capacity, specific targeting properties, and long-term stability is highly desirable in cancer therapy. Abstract : Exploration of an efficient dual-drug based nanocarrier with high drug loading capacity, specific targeting properties, and long-term stability is highly desirable in cancer therapy. Metal–organic frameworks (MOFs) have proven to be a promising class of drug carriers due to their high porosity, crystalline properties with defined structure information, and their potential for further functionalization. To enhance the drug efficacy as well as to overcome the burst effect of drugs, here we synthesized a pH responsive folic acid (FA) and graphene oxide (GO) decorated zeolitical imidazolate frameworks-8 (GO–FA/ZIF-8), for targeted delivery of doxorubicin (DOX) and cyclophosphamide (CP), simultaneously. In this system, DOX molecules were encapsulated in the pores of ZIF-8 during in situ synthesis of ZIF-8 and CP molecules have been captured by the GO surface via hydrogen bonding and π–π interactions as well. Furthermore, the resulting pH-responsive nanocarrier (DOX@ZIF-8/GO–FA/CP) showed in vitro sustained release characteristics (76% of DOX and 80% of CP) by cleavage of chemical bonding and disruption of the MOFs structure under acidic condition (at pH 5.6). Moreover, DOX@ZIF-8/GO–FA/CP has synergistic cytotoxic effects as compared to the combination of both the drugs without ZIF-8/GO–FA when treating MCF-7 and MDA-MB-231 breast cancer cell lines (with a combination index of 0.29 and 0.75 for MCF-7 and MDA-MB-231 cell-lines, respectively). Hence this system can be applied as an effective platform for smart dual drug delivery in breast cancer treatment through its remarkable manageable multidrug release.